BIOFABRICATION OF SILVER NANOPARTICLES FROM FRUITS WASTE EXTRACT AND THEIR APPLICATION TOWARDS ANTIMICROBIAL ACTIVITY - N. KIRUTHIKA; T. SOMANATHAN (International Journal of Pharma and Bio Sciences, 2016)
The development of uniform nanoparticles has been intensively pursued because of their technological and fundamental scientific importance. In this work, we have formulated a simple and effective procedure for biofabrication of silver nanoparticles (AgNPs) using fruit waste extract. The resulting AgNPs were characterized by UV-Visible spectroscopy, Fourier Transform Infra Red (FT-IR) Spectroscopy and Transmission electron microscopy (TEM) techniques. The UV-visible spectra of the silver nanoparticles showed an adsorption peak at 410 nm. The TEM image reveals that the uniformly dispersed AgNPs with a uniform size and shape in the average size of 6 nm. Biosynthesised AgNPs were studied for antimicrobial activity against the human pathogenic bacteria’s (Proteus, Klebsiella). These nontoxic nanoparticles which can be prepared in a biosynthesis method prove to be potential candidates for medical applications.